Primer Design of EDNRB Gene Exon 5 and PCR Optimization for Gene Mutation Analysis in Hirschsprung's Disease - Anggun, Septiasri; Ahda, Yuni (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
HD disease is a common cause of neonatal intestinal obstruction. HD disease is a congenital disorder of the colon characterized by the absence of parasympathetic ganglion cells in the sub mucosal plexus of Meissneri and the mienterikus plexus of Auerbachi. Objective: To design specific primers for amplification of exon 5 in EDNRB gene and test the specificity in silico. To determine the optimum PCR conditions for amplification of exon 5 in EDNRB gene. Methods This type of research is descriptive. The purpose of descriptive research is to provide an overview or description of the EDNRB exon 5 gene primer design and PCR optimization. Electrophoresis results showed the temperature of 56 oC is the right temperature characterized by a single band and looks the thickest and brightest with the appropriate amplicons size of 367 bp, The results for the EDNRB gene primer exon 5 obtained the optimum concentration of 0.8 µM. This is characterized by DNA bands that look clear and thickest. The specific sequence of forward primer is 5'ATTTCA GAGACG GGAAG TGG3' reverse primer is 5'GGCACT CACTCATCATCTTG 3' which produces amplicons with a length of 367 bp. The optimum annealing temperature is 56 oC and the optimum primer concentration is 0.8 µM.